Analisis Pengetahuan dan Sikap Orang Tua Terhadap Pertolongan Pertama Pada Anak dengan Situasi Gawat Darurat Seperti Tersedak, Kejang, dan Sesak - Irindy Inayah Usman; Setiawati; Rudi Winarno (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2026)
Background: When a child experiences an emergency condition, immediate management is crucial to prevent complications, disability, or even death. However, many parents still lack understanding of how to provide first aid, either at home or in public places. Parents’ knowledge and attitudes greatly influence the success of initial actions taken before medical help arrives. Objective: To analyze parents’ knowledge and attitudes in providing first aid to children in emergency situations at Dr. H. Abdul Moeloek General Hospital in 2025. Method: This study used an analytic survey method with a cross-sectional approach, involving 33 parents who had children aged 1–12 years hospitalized at the time of the study. The sample was selected using an accidental sampling technique. Respondents filled out a questionnaire, and the data were analyzed using frequency distribution and chi-square tests. Results: The univariate analysis showed that 60.6% of respondents had poor knowledge, 51.5% had a positive attitude, and 66.7% did not perform first aid. The bivariate analysis revealed p-values of 0.009 for knowledge and 0.036 for attitude. Conclusion: There is a significant relationship between knowledge and attitude with parents’ actions in providing first aid. Recommendation: Parents are encouraged to actively seek information and participate in first aid training organized by community health centers, the Indonesian Red Cross (PMI), or hospitals.